"The Lifeline" of Technical Systems in a TRIZ-LEAN Environment. (2015) - Navas, Helena V.G.; Machado, Virgílio A. Cruz
Abstract: The last decades are characterized by globalization of markets and increase of their competitiveness. Enterprises need to enable the quick satisfaction of customer demands and to improve their products and services continuously. Lean Thinking goal is a creation of streamlined work processes with minimized inventory, maximized throughput, without backlog and bureaucracy[1] . The life cycle curve shows how the main characteristics of a system change in time. The main characteristics of a system can be, for example, power, productivity, speed, etc. In "childhood" the development of the technical system is slow. Next comes the time of "growth" and "maturity" with rapid improving and massive use of the technical system. Then comes a moment of development rhythm decreasing and "old age" begins. Next two alternatives are possible: the technical system deteriorates, becoming a fundamentally different system, or keeps performance for a long time. This article examines the "lifeline" of technical systems in a Lean environment and how TRIZ may be used to provide organizations with tools to determine the best way for all "old stages" of technical systems. There are several TRIZ tools which can be used to look for Lean wastes and to solve contradictions (eliminate wastes, by Lean approach).